Application of Advanced Microscopic Methods to Study the Interaction of Carboxylated Fluorescent Nanodiamonds with Membrane Structures in THP-1 Cells: Activation of Inflammasome NLRP3 as the Result of Lysosome Destabilization - Knötigová, Pavlína Turánek; Mašek, Josef; Hubatka, František; Kotouček, Jan; Kulich, Pavel; Šimečková, Pavlína; Bartheldyová, Eliška; Machala, Miroslav; Švadláková, Tereza; Krejsek, Jan; Vaškovicová, Naděžda; Skoupý, Radim; et al. (Molecular pharmaceutics, 2019)
Nanodiamonds (ND), especially fluorescent NDs, represent potentially applicable drug and probe carriers for in vitro/in vivo applications. The main purpose of this study was to relate physical-chemical properties of carboxylated NDs to their intracellular distribution and impact on membranes and cell immunity-activation of inflammasome in the in vitro THP-1 cell line model. Dynamic light scattering, nanoparticle tracking analysis, and microscopic methods were used to characterize ND particles and their intracellular distribution. Fluorescent NDs penetrated the cell membranes by both macropinocytosis and mechanical cutting through cell membranes. We proved accumulation of fluorescent NDs in lysosomes. In this case, lysosomes were destabilized and cathepsin B was released into the cytoplasm and triggered pathways leading to activation of inflammasome NLRP3, as detected in THP-1 cells. Activation of inflammasome by NDs represents an important event that could underlie the described toxicological effects in vivo induced by NDs. According to our knowledge, this is the first in vitro study demonstrating direct activation of inflammasome by NDs. These findings are important for understanding the mechanism(s) of action of ND complexes and explain the ambiguity of the existing toxicological data.
Keywords: cathepsin B; lysosomal disruption; THP-1 Cells; kathepsin B; nanodiamanty; Lysosomes; Pinocytosis; konfokální mikroskopie; dynamický rozptyl světla; THP-1 buňky; macropinocytosis; NLR Family, Pyrin Domain-Containing 3 Protein; AFM; Microscopy, Atomic Force; TEM; inflammasome NLRP3; Inflammasomes; elektronová mikroskopie; pinocytóza; lyzozomy; mikroskopie atomárních sil; Fluorescence; Microscopy, Confocal; Cell Membrane; protein NLRP3; lidé; Nanodiamonds; Humans; Microscopy, Electron; buněčná membrána; Intravital Microscopy; fluorescence; inflammation; fluorescent nanodiamonds; inflamasomy; THP-1 cells; Cathepsin B; cathodoluminescence; cell immunopathology; intravitální mikroskopie; Dynamic Light Scattering; nanodiamond intercellular distribution